Role descriptions induce gender mismatch effects in eye movements during reading - Reali, Chiara; Esaulova, Yulia; Öttl, Anton; von Stockhausen, Lisa (Frontiers in Psychology, 2015)
The present eye-tracking study investigates the effect of gender typicality on the resolution of anaphoric personal pronouns in English. Participants read descriptions of a person performing a typically male, typically female or gender-neutral occupational activity. The description was followed by an anaphoric reference (he or she) which revealed the referent's gender. The first experiment presented roles which were highly typical for men (e.g., blacksmith) or for women (e.g., beautician), the second experiment presented role descriptions with a moderate degree of gender typicality (e.g., psychologist, lawyer). Results revealed a gender mismatch effect in early and late measures in the first experiment and in an early measure in the second experiment. Moreover, eye-movement data for highly typical roles correlated with explicit typicality ratings. The results are discussed from a cross-linguistic perspective, comparing natural gender languages and grammatical gender languages. An interpretation of the cognitive representation of typicality beliefs is proposed.